DEVELOPMENT OF AGE RELATED REFERENCE RANGES FOR THE HCG STIMULATION TEST IN CHILDREN WITH SUSPECTED DISORDERS OF ADROGENISATION. (February 2015) - Choong, Wai Keong; Choy, Kay Weng; Brown, Justin; Bergman, Phil; Doery, James C. G.
Abstract : Introduction: The HCG stimulation test is an important investigation to assess testicular function in infants with disorders of sexual differentiation. Although this test has been used over many years, interpretive guidelines, particularly age related reference ranges are ill-defined. Aim: To establish age related testosterone and dihydrotestosterone responses, and testosterone/dihydrotestosterone T/DHT ratios. Methods: An audit of clinical and biochemical pathology records in 63 children given HCG stimulation tests was performed and reviewed according to age. Testosterone was measured by immunoassay in 70% of patients and subsequently by LC-MS/MS. DHT was measured by RIA throughout. Results: The 72 h post-HCG testosterone response was highly age related. The upper limit increased from about 15 nmol/L in the first week of life to about 28 at 3 months of age and then declined to < 10 at 2 years until the commencement of puberty when maximal response was > 10. The minimal response in normal patients will be discussed but was more difficult to define due to imprecise establishment of final diagnosis. Conclusion: While these interim results will assist interpretation of HCG stimulation tests this ongoing study will benefit from increasing accumulation of data across the entire pediatric age range and the increased accuracy of testosterone and especially DHT with the development of LC-MS/MS for DHT assay.